8(x-9)-9(x-8)=x+7-(x-1)

Simple and best practice solution for 8(x-9)-9(x-8)=x+7-(x-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8(x-9)-9(x-8)=x+7-(x-1) equation:


Simplifying
8(x + -9) + -9(x + -8) = x + 7 + -1(x + -1)

Reorder the terms:
8(-9 + x) + -9(x + -8) = x + 7 + -1(x + -1)
(-9 * 8 + x * 8) + -9(x + -8) = x + 7 + -1(x + -1)
(-72 + 8x) + -9(x + -8) = x + 7 + -1(x + -1)

Reorder the terms:
-72 + 8x + -9(-8 + x) = x + 7 + -1(x + -1)
-72 + 8x + (-8 * -9 + x * -9) = x + 7 + -1(x + -1)
-72 + 8x + (72 + -9x) = x + 7 + -1(x + -1)

Reorder the terms:
-72 + 72 + 8x + -9x = x + 7 + -1(x + -1)

Combine like terms: -72 + 72 = 0
0 + 8x + -9x = x + 7 + -1(x + -1)
8x + -9x = x + 7 + -1(x + -1)

Combine like terms: 8x + -9x = -1x
-1x = x + 7 + -1(x + -1)

Reorder the terms:
-1x = x + 7 + -1(-1 + x)
-1x = x + 7 + (-1 * -1 + x * -1)
-1x = x + 7 + (1 + -1x)

Reorder the terms:
-1x = 7 + 1 + x + -1x

Combine like terms: 7 + 1 = 8
-1x = 8 + x + -1x

Combine like terms: x + -1x = 0
-1x = 8 + 0
-1x = 8

Solving
-1x = 8

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Divide each side by '-1'.
x = -8

Simplifying
x = -8

See similar equations:

| 2x+2=-38-2x | | -1/14-9/14 | | -k+3k+9k+5k=0 | | 5*6+y=20 | | 3(x-1)+2x=19 | | (7n-3)/8=n-1 | | 10x-(4y+8)=-20 | | 7h+5=19 | | 8=11h | | 0=t^2-8t-12 | | f(x)=(x-4)^1/2 | | 8b-6(b-4)=31-5b | | -.75x+8=14 | | 13=25(6x+15) | | -18x^5-10x^2+8x=0 | | 13 = 25(6x+15) | | 9X+4x-7x-5=7 | | -3x+27=6-4x | | 6.8n-32=4.4n+2 | | 2x-10+y=180 | | 82=-8r+90 | | 5x+20=6-2x | | R/8=-24 | | 6q=6(4+1) | | 5x+3(0.05)=4x+7(0.05) | | 240=(l*2)+(20*2) | | 240=(l*2)+(w*2) | | 15.50+x=9.75 | | 4(5x+2)=4(3x+2) | | (12x-7)+(13-4x)= | | y=26+4x | | p-3(p-1)=2+(2p+5) |

Equations solver categories